A novel approach to include social costs in humanitarian objective functions - Florian Diehlmann; Patrick S. Hiemsch; Marcus Wiens; Markus Lüttenberg; Frank Schultmann (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2020)
Social cost functions in humanitarian operations are defined as the sum of logistics and deprivation costs. They are widely regarded as appropriate objective functions, even though the way they were introduced requires cautiously formulated deprivation cost functions for the analyzed goods and do not allow decision makers to include their individual preferences. We develop this approach further and introduce a normalized weighted sum approach to increase decision makers' understanding of the tradeoffs between cost and suffering and, therefore, increase transparency significantly. Furthermore, we apply the approach to a case study of a hypothetical water system failure in the city of Berlin. We show that the normalized weighted sum approach significantly improves transparency and leads to a deeper understanding of the tradeoffs during the crisis. Consequently, it proved itself as a powerful tool for decision makers preparing for or navigating through a crisis.
Keywords: 330; humanitarian logistics; social cost; deprivation cost; facility location planning